Syringe Pump With Nearly Empty Based Microcontroller Atmega328 - Lely Erica Putri; Muhammad Ridha Mak'ruf; Abd Kholiq (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2019)
Syringe Pump is a tool used to give liquid medicine or food liquid into the patient's body in a certain amount and within a certain period of time on a regular basis. The purpose of this study is to facilitate monitoring of fluid in the syringe so that the hose is not installed continuously when the liquid has run out. The circuit consists of an Atmega328 microcontroller, a motor driver, and an optocoupler sensor. Setting the syringe, volume and flowrate is done at the beginning. To insert liquid, the motor must be run by the way the settings have been done and press the start button. Tools need supply from PLN grids. Calibration is done using IDA 4 Plus. This tool is equipped with the addition of alarms nearly empty and the bolus button. From the measurements taken, at the 20 ml syringe the biggest error occurred at the 5 ml volume point of 0.4% and at the 50 ml syringe the biggest error occurred at the 5 ml volume point of 0.280%.This module can be used according to its function, because the% error is still below the ± 5% standard.